Hutan dalam Mite Mambang Tawuong Asam (Sebuah Tafsir atas Cerita Lisan Teluk Meranti) - Alvi Puspita; Hendra Hendra (Antropologi Indonesia, 2014)
Each community has a inherited mite from generation to generation, as well as MambangTawuong Asam myth. As a form of oral tradition, myth Mambang Tawuong Asam into thescheme of the analysis the state of society in forest utilization around Teluk Meranti. Theanalysis is used to connect fragments of myth in which actors in the myths associated withthe presence of forests as did William R Bascom against the myth. The results obtained thatthe youngest daughter represent the image of a simple Malay people who later married theMambang.Meanwhile the brothers of the youngest daughter anxiously awaited for a rich,handsome, and smart prince; in this episode is referred to as a happy simple, greedy vain.While in the second part, the youngest daughter and Mambang was separated because of thedeath Mambang (loss of Mambang’s faith value), while the youngest daughter’s brothers metwith the idol prince from across the country who intends to dominate the forest; The secondepisode is called simple that miserable, greedy prosperous.Keyword: Myth, Oral Tradition, Mambang Tawuong Asam